Serious games for the human behaviour analysis in emergency evacuation scenarios - Almeida, João Emílio (2019)
This paper describes an experiment designed to elicit human behaviour when facing the urgent need of exiting an unknown building. This work is part of a larger effort to devise the methodological approach underlying the implementation of simulation of pedestrians and elicitation of their emergent dynamics, an experimental framework coined SPEED. To validate our experimental setup, a group of 16 experts on fire safety, emergency planning and building evacuation were consulted. The experts were solicited to answer a questionnaire, rating their gaming experiences and validating the questions in the form to be presented to subjects. Their comments were valuable inputs used in the development of the experiment described in this paper. A sample of 62 subjects was then used to test our approach, which consists in having the subjects answering a questionnaire and later on playing a Serious Game resorting to the Unity3D game engine. Some specific scenarios were carefully designed and presented to subjects, both in the questionnaire and in the game environment to maintain consistency of answers. Preliminary results are promising, showing that the challenge made players think about the various situations that might happen when facing an emergency. They are also implied to reason on their stream of decisions, such as which direction to take considering the environment and some adverse situations, such as smoke, fire and people running on the opposite direction of the emergency signage.